Exploring The Electoral Strategies of Major Political Parties In Jammu And Kashmir In The Post-2002 Era - Rasool, Tabasum; Nawaz, Saqib; Parry, Suheel (International Journal of Psychosocial Rehabilitation, 2020)
The political landscape of Jammu and Kashmir (J&K) has undergone significant transformations since 2002, marked by shifts in voter demographics, evolving security dynamics, and broader national trends. This study explores the electoral strategies of major political parties in J&K, including the Jammu and Kashmir National Conference (NC), the Jammu and Kashmir Peoples Democratic Party (PDP), the Bharatiya Janata Party (BJP), and the Indian National Congress (INC). The research examines how these parties have adapted to changing political realities, voter expectations, and socioeconomic conditions. Key findings highlight the PDP's focus on youth engagement and reconciliation, the BJP's emphasis on development and national integration, and the NC and INC's advocacy for regional autonomy and inclusive development. These strategies reflect the parties’ efforts to navigate J&K's complex socio-political environment and secure electoral success.